Entre dissidence politique et dissidence littéraire : le dialogue Marguerite de Valois-Brantôme - Éliane Viennot (Les Dossiers du GRIHL)
This essay interrogates the work of two of the most important memoire-writers of the French Renaissance: Brantôme and Marguerite de Valois, works born of their social standing as members of an elite in conflict with power as well as their ongoing dialogue with one another. Having traced the political trajectory of each one of these authors and mapped the states of mind which brought them to the memorialist enterprise, the essay focuses at once on the political dissidence and the literary inventiveness of these authors, different as these prove to be. The Queen’s work would eventually become a model for the great genre of aristocratic Memoirs while the work of her admirer would remain a hapax.  Finally, the essay aims to show that the freedom of expression, demonstrated in a different way by each of these authors, is  closely related to their position as opponents and modulated by the stakes of their dialogue